Chemical Sensor for Detection of Lead Levels in Herbal Medicine - Ani Mulyasuryani; Yuniar Ponco Prananto; Elvian Eka Krisnaniningrum (Universitas Jenderal Soedirman, 2021)
A new tube type Pb2+ sensor made from two types of mixtures, namely clay-PbI2 and chitosan-PbI2 were prepared. An electromotive force (EMF) with Ag/AgCl as the reference electrode was used as the output signal. The highest performance of the Pb2+ sensor from clay-PbI2 was obtained at Pb2+ solutions in HNO3 and pH 3 with sensor sensitivity of 20.67 mV/decade. The highest performance of the Pb2+ sensor from chitosan-PbI2 was obtained at Pb2+ solutions in demineralized water with sensor sensitivity of 32.49 mV / decade. Application of the two sensors on several commercial herbal samples resulted in an average recovery of 85.62% and 94.10% for sensor from chitosan-PbI2 and clay-PbI2, respectively